SISTEM INFORMASI AKADEMIK PADA SMA N 1 PALEMBAYAN BERBASIS WEB MENGGUNAKAN FRAMEWORK BOOTSTRAP - Nelfira Nelfira; Amuharnis Amuharnis; Elizamiharti Elizamiharti; Cindy Wiriani (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2021)
Academic Information System (SIA) or Sistem Information Akademik (SIA) is an information system created to help the process of processing all school civitas data designed to assist the processing of all data of the school community. At SMA N 1 Palembayan, grades, school civitas biodata, and enrollment of new students still utilize simple applications from Dapodik and Ms. Office applications and archived in the form of paper that causes data to be vulnerable to damage, and lost. In addition, the entire community of schools and the general public is difficult and slow in obtaining school information if at any time needed due to the dissemination of information that is still manual. Therefore, to facilitate schools in the effective and efficient processing and dissemination of information, a web- based academic information system is needed. This academic information system was developed using PHP programming language with MySql storage media and supported by other programs. The final result of this research is the creation of a web-based academic information system that can present academic and non- academic information to schools easily and quickly for both the school community and the general public.